Studi Kesesuaian SNI 8748:2019 Terhadap Partisipasi Pengelolaan Pendakian Gunung Oleh Masyarakat di Kawasan Hutan Lindung Salahutu - Wakano, Baqum; Tjoa, Martina; Iskar, Iskar (Universitas Pattimura, 2024)
Mountain climbing is an outdoor activity that has risks. SNI 8748:2019 about mountain climbing management by the technical committee of forest management under the Indonesian Ministry of Forestry. Its function is to make the stakeholders optimize the activity of mountain climbing. This research aims to determine the compatibility between SNI 8748:2019 with mountain climbing management by the communities of two villages in The Salahutu Protected Forest Area. The research’s samples were taken using purposive sampling and accidental sampling. Data analysis uses Miles & Hubermann Theory and measuring instrument of SNI 8748 (Pusfaster, 2019). The result of research that the communities of two villages participate in the form of thoughts, energy, items, and skills. Meanwhile, participation of money was not found. There is percentage of conformity with measuring instrument SNI 8748:2019 in Waai Village amount of 43,75% and 23,43% in Morella Village.